CuOx-TiO2 composites: electronically integrated nanocomposites for solar hydrogen generation - Bharad, Pradnya A.; Nikam, Arun, V.; Thomas, Femi; Gopinath, Chinnakonda S. (ChemistrySelect, 2018)
CuOx-TiO2 (CT) composites were prepared by different methods (impregnation, microwave and photodeposition methods) and evaluated for solar water splitting (SWS) with aqueous methanol. CT composites prepared by three different methods were characterized by relevant methods to understand the correlation between synthesis method and activity, and the mechanism of water splitting. A comparison of photocatalytic activity of CT composite materials indicates that the photocatalyst prepared by photodeposition method shows significantly improved activity for hydrogen production from aqueous methanol as well as with water (overall water splitting) under one sun conditions. Cu is present in Cu/Cu+1 form in photodeposition method prepared CT, which is more effective and helpful for solar light absorption as well as charge carrier separation due to the formation of bulk p-n (Cu2O-TiO2) heterojunctions. However, CuO formation seems to decrease the activity with other preparation methods.